Industrial training report: Tenaga Nasional Berhad Kuala Lipis / Aisyah Mohamad Mokhtar - Mohamad Mokhtar, Aisyah (Faculty of Business and Management, 2025)
From 12 August 2024 to 24 January 2025, I completed my industrial training at Tenaga Nasional Berhad (TNB) Branch Kuala Lipis, which is fully detailed in this report. I have gained a lot of information from my internship, which has focused on applying academic knowledge and comprehending one of the top administrative entities. Business Support Office and Retail, SME & Resident were among the units I had the opportunity to work with during my internship. Managing paperwork, attending meetings and interacting with customers were all part of my organized responsibilities. I might be able to get insight into the working world through such hands-on experience. Both the actual experience in operations and the communication skills I acquired from my internship were excellent. I also learnt a lot from administrators in any firm about document management, customer service and the need of maintaining the highest standards. It was an extremely enriching internship at TNB Lipis. My career development was greatly aided by my time in this program. I'm sure the knowledge that I gained from this will be crucial to the advancement of my profession. My future career is kept on a highly beneficial path by the mentors and team I worked with at TNB. I am so grateful to the staff at TNB Kuala Lipis for their guidance and assistance.